Hydrogel evaporator for generating power through solar evaporation and preparation method of hydrogel evaporator

By using PVA matrix combined with TOCNFs and SLS in a solar-powered interfacial evaporation system to prepare low latent heat hydrogel evaporators, the limitations of existing systems in environmental changes and evaporation rate improvement are solved, and efficient seawater desalination and power generation are achieved.

CN119503937APending Publication Date: 2025-02-25QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)

Patent Information

Application Number
CN202411629119.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing solar-powered interface evaporation systems have limitations in environmental changes and evaporation rate improvement, making it difficult to achieve efficient seawater desalination and power generation.

Method used

Polyvinyl alcohol (PVA) is used as the matrix, combined with Tempo oxidized cellulose nanofibers (TOCNFs) and sodium lignin sulfonate (SLS), and a low latent heat hydrogel evaporator is prepared by a simple method. The liquid nitrogen directional freezing and freeze-drying process is used to achieve a solar evaporation-power generation integrated solar evaporator.

Benefits of technology

It achieves efficient seawater desalination and power generation, has excellent mechanical properties and environmental adaptability, can maintain a high evaporation rate in high-intensity sunlight and high-concentration brine solutions, and can continuously generate open circuit voltage for more than 7 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503937A_ABST
    Figure CN119503937A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrogel evaporator for generating power by solar evaporation and a preparation method thereof, PVA is dissolved in deionized water to prepare a PVA solution, and then TOCNFs and SLS are added to prepare a polyvinyl alcohol / Tempo oxidized cellulose nanofiber / sodium lignin sulfonate (PTFS) suspension. Adding glutaraldehyde (GA) into the prepared suspension liquid, and adding a phytic acid solution (PA) and a multiwalled carbon nanotube dispersion liquid (CNT) after the suspension liquid is fully mixed, so as to prepare a PTFS hydrogel precursor solution; and directionally freezing the precursor solution by using liquid nitrogen, and finally freeze-drying to obtain the evaporation-power generation integrated low-latent-heat hydrogel evaporator. The prepared evaporator can generate clean water and electric power at the same time, and multi-stage utilization of energy is achieved. And the material also has excellent mechanical properties, is rich in internal water transmission channels, and has better adaptive capacity to the environment. The ultra-high evaporation rate can still be kept under high-intensity sunlight and in a high-concentration saline solution, and the seawater desalination efficiency of the solar evaporator is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photothermal material engineering, and specifically relates to a hydrogel evaporator that generates electricity by utilizing solar evaporation and a preparation method thereof. Background Art

[0002] Freshwater resources and energy are two basic elements for maintaining the sustainable development of human civilization and society. Energy shortages urgently require innovative integration of solar evaporation systems and power generation systems. Solar-driven interfacial evaporation is an emerging zero-energy technology for seawater desalination with broad prospects for utilization. At present, there are some technologies that can convert the movement of water or steam into electricity, such as friction nanogenerators and hydrovoltaic generators. Among them, evaporation-induced hydrovoltaic power generation can generate electrical signals using the natural evaporation process that occurs all the time in the environment, which has attracted widespread attention. Combining interfacial evaporation with hydrovoltaic power generation through reasonable structural design is expected to achieve the simultaneous collection of clean water and electricity.

[0003] Existing related work has studied and developed an integrated evaporation-power generation device to promote clean water and electricity production. Due to water management constraints, this type of integrated device usually requires tilting or encapsulating electrodes to ensure that the asymmetric wetting structure is always maintained during the evaporation process, and is sensitive to environmental changes. In addition, increasing the evaporation rate can promote electricity generation. Therefore, constructing a hydrogel evaporator with hierarchical nanochannels and low latent heat to adapt to different environmental conditions provides a new way to improve the utilization of solar energy. Hydrogel materials with widely tunable properties are strong candidates for integrated evaporation and power generation, which is expected to alleviate the severe situation of shortage of freshwater resources and electrical energy. The use of hydrogels to prepare low latent heat solar energy for evaporation power generation has not been reported. Summary of the invention

[0004] The purpose of the present invention is to provide a hydrogel evaporator for generating electricity by solar evaporation and a preparation method thereof. We use commercially available common polyvinyl alcohol (PVA) as a frame, Tempo oxidized cellulose nanofibers (TOCNFs, 1% solid content) and sodium lignin sulfonate (SLS) to prepare a low-latency hydrogel solar evaporator that can achieve seawater desalination and electricity generation using a simple method.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] PVA was dissolved in deionized water to prepare a PVA solution, and then TOCNFs and SLS were added to prepare a polyvinyl alcohol / Tempo oxidized cellulose nanofiber / sodium lignin sulfonate (PTFS) suspension. Glutaraldehyde (GA) was added to the prepared suspension, and after sufficient mixing, phytic acid solution (PA) and multi-walled carbon nanotube dispersion (CNT) were added to prepare a PTFS hydrogel precursor solution. The precursor solution was directionally frozen with liquid nitrogen, and finally freeze-dried to obtain a low-latency hot water gel evaporator with evaporation and power generation.

[0007] More specifically, the preparation method of the hydrogel evaporator using solar energy evaporation to generate electricity is as follows:

[0008] (1) Preparation of PTFS suspension:

[0009] 1 part (mass) of PVA was dissolved in 10 parts (volume) of deionized water at 90°C and cooled to room temperature. 2-6% of TOCNFs (1% solid content) and 10-30% of SLS were added to the PVA solution and mixed thoroughly to prepare a uniform PTFS suspension.

[0010] (2) Preparation of PTFS precursor solution:

[0011] 0.125 parts (volume parts) of GA solution (concentration of 50%) were added to the PTFS suspension and stirred for 5 minutes. Subsequently, 1wt% of PA solution (concentration of 70%, water content of 30%) and 2wt% of CNT solution (concentration of 14%, water content of 86%) were added to the PTFS suspension and stirred evenly to prepare a PTFS hydrogel precursor solution.

[0012] (3) Directed freezing of PTFS hydrogel precursor

[0013] The PTFS precursor solution prepared in step (3) is placed in a liquid nitrogen environment, and the precursor solution is directional-frozen from bottom to top through a heat sink, and taken out after being completely frozen. Finally, freeze-drying is performed at a temperature of -54°C for 48 hours to obtain a PTFS hydrogel evaporator, i.e., a low-latency hot water gel solar evaporator for evaporation power generation of the present invention.

[0014] The present invention experiments on the effects of different TOCNFs and SLS contents on the evaporation performance of the evaporator, and concludes that, compared with the PVA solution, 6wt% of TOCNFs is the optimal dosage, and 20wt% of SLS is the optimal dosage.

[0015] A specific example is:

[0016] (1) Preparation of PTFS suspension:

[0017] 1 g (mass fraction) of PVA was dissolved in 10 g (mass fraction) of deionized water at 90°C and cooled to room temperature. 2 wt% of TOCNFs (1% solid content) and 10 wt% of SLS were added to the PVA solution and mixed thoroughly to prepare a uniform PTF 2% SLS. 10 % suspension.

[0018] (2) Preparation of PTFS precursor solution:

[0019] 0.125 μl of GA solution with a concentration of 50% was added to the PTFS suspension and stirred for 5 minutes. Subsequently, 1 wt% (i.e. 0.29 g) of PA solution (concentration of 70%) and 2 wt% (i.e. 0.71 g) of CNT solution (concentration of 14%) were added to the PTFS suspension and stirred evenly to prepare a PTFS hydrogel precursor solution.

[0020] (3) Directed freezing of PTFS hydrogel precursor

[0021] The PTFS precursor solution prepared in step (3) is placed in a liquid nitrogen environment, and the precursor solution is directionally frozen from bottom to top through a heat sink, and taken out after being completely frozen. Finally, freeze-drying is performed at a temperature of -54°C for 48 hours to obtain the product.

[0022] In addition, the hydrogel evaporator prepared by the above preparation method and its application in seawater desalination and power generation also fall within the protection scope of the present invention. The application includes but is not limited to the application in seawater desalination and power generation. As long as the hydrogel evaporator obtained by the preparation method of the present invention falls within the protection scope of the present invention.

[0023] Advantages of the present invention:

[0024] 1. The PVA selected in the present invention is a water-soluble linear polymer with rich hydroxyl groups, which is non-toxic, highly stable and has excellent biocompatibility. TOCNFs and SLS are innovatively introduced into PVA-based hydrogels, wherein TOCNFs can form a high-strength and dense porous material, and polar groups such as phenolic hydroxyl and alcoholic hydroxyl exist in the molecular structure of SLS, which has a certain antibacterial effect. The oxygen-containing functional groups in TOCNFs and SLS easily form weak hydrogen bonds with water molecules, reducing the energy required for water evaporation. The prepared evaporator can produce clean water and electricity at the same time, realizing the multi-level utilization of energy.

[0025] 2. The prepared evaporator has excellent mechanical properties, abundant internal water transmission channels, and better environmental adaptability. It can still maintain an ultra-high evaporation rate under high-intensity sunlight and high-concentration salt water solution, improving the desalination efficiency of the solar evaporator.

[0026] 3. The solar evaporator prepared by the present invention can continuously generate an open circuit voltage for more than 7 hours and remain stable.

[0027] 4. The preparation process of the present invention is simple, the raw materials are easily available, the effect is remarkable, and it has effective antibacterial properties to ensure that the clean water produced is harmless to the human body, so it has high application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the preparation process of the present invention.

[0029] Figure 2 The influence of TOCNFs content on the mechanical properties of the evaporator.

[0030] Figure 3 It is the influence of different TOCNFs content on the evaporation performance of the evaporator; in the figure, a: the influence of TOCNFs content on the surface temperature of the evaporator; b: the influence of TOCNFs content on the evaporation rate of the evaporator; c: the influence of TOCNFs content on the latent heat of the evaporator.

[0031] Figure 4 It is the influence of different SLS contents on the evaporation performance of the evaporator; in the figure, a: the influence of SLS content on the surface temperature of the evaporator; b: the influence of SLS content on the evaporation rate of the evaporator; c: the influence of SLS content on the latent heat of the evaporator.

[0032] Figure 5 is the power generation performance of the PTFS evaporator; in the figure, a: Zeta potential of PVA and PTFS evaporators; b: voltage of PVA and PTFS evaporators; c: voltage change of PTFS with or without light conditions.

[0033] Figure 6 This is a SEM image of the cross section of the evaporator; in the figure, a: PVA, b: PTF 2% S 0% 、c:PTF 4% S 0% and d:PTF 6% S 0% SEM image of the cross section.

[0034] Figure 7 is the indoor evaporation performance of the PTFS evaporator; in the figure, a: PTF 6% S 20% Mass variation under 0.5 to 3 suns; b: PTF 6% S 20% Evaporation measurement over 10 cycles in simulated seawater; c: Evaporation rate of the evaporator in 3.5 wt% NaCl solution.

[0035] Figure 8 PTF 6% S 20% Outdoor evaporation performance of the evaporator.

[0036] Fig. 9 PTF 6% S 20% The salt removal and seawater desalination capacity of the evaporator. In the figure, a is PTF 6% S 20% Desalination of evaporator; b is the UV-visible absorption characteristics of rhodamine B (RhB) and methylene blue (MB) before and after purification of simulated industrial wastewater. The figure shows the images of RhB solution (left) and MB solution (right) before and after purification. c is the concentration of major metal ions in the initial seawater and the water collected after desalination.

[0037] Fig.10 PTF 6% S 20% The power generation performance of the evaporator. In the figure, a is PTF 6% S 20% The voltage and current density of the load are shown in Figure 2. b is the power density as the load increases; c is the measured PTF 6% S 20% Voltage under unsealed and sealed conditions.

[0038] Fig.11 PTF 6% S 20% Measured voltage of the evaporator under 1 sun exposure.

[0039] Fig.12 9 PTFs in series 6% S 20% The unit drives a digital image of a timer. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with specific examples, and the advantages and features of the present invention will become clearer as the description proceeds. However, the specific experimental methods involved in the following examples are all conventional methods or implemented under the conditions recommended by the manufacturer's instructions unless otherwise specified.

[0041] Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. The test methods in the following examples are conventional methods unless otherwise specified. Unless otherwise specified, the reagents and materials used can all be purchased from the market.

[0042] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only.

[0043] The PTFS in the present invention stands for polyvinyl alcohol / Tempo oxidized cellulose nanofibers / sodium lignin sulfonate, the TOCNFs are Tempo oxidized cellulose nanofibers, the SLS is sodium lignin sulfonate, the GA is glutaraldehyde, the PA is phytic acid, and the CNT is a multi-walled carbon nanotube dispersion. The following experiments all use abbreviated forms to represent them.

[0044] The present invention dissolves PVA in deionized water to prepare a PVA solution, and then adds TOCNFs and SLS to prepare a PTFS suspension. GA is added to the prepared suspension, and PA and CNT are added after sufficient mixing to prepare a PTFS hydrogel precursor solution. The precursor solution is directionally frozen with liquid nitrogen, and finally freeze-dried to obtain an evaporation-power generation integrated low-latency hot water gel evaporator ( Figure 1 ).

[0045] Using the above ideas, some influencing factors in the experiment were discussed, as follows:

[0046] 1. Effect of TOCNFs content on the mechanical properties of evaporator

[0047] PTFS with hierarchical nanostructures was prepared by chemical cross-linking and directional freezing. This spatial structure not only ensures water transport during evaporation, but also has good mechanical properties. To evaluate the mechanical properties of the evaporator, compression tests were performed on the original PVA evaporator and PTFS evaporator with different additions of TOCNFs ( Figure 2 ). The stress of the original PVA evaporator at 80% strain was only 330 kPa. However, the incorporation of TOCNFs significantly improved the mechanical properties of the hydrogel. Specifically, as the amount of TOCNFs added increased, the stress level in the hydrogel gradually increased, reaching a maximum value of 495 kPa.

[0048] First, the mass fraction of SLS in the system was determined to be 20%, and the concentration of TOCNF was changed. The more TOCNF content, the greater the viscosity of the system solution. When the concentration increased to 8%, the solution viscosity would affect the dispersion effect of other substances, so the concentration of 8% and above was no longer discussed.

[0049] 2. Effect of TOCNFs content on evaporation performance of evaporator

[0050] Figure 3Figure a shows the temperature change curve of the evaporator under 1 sunlight irradiation. Under 1 sunlight irradiation, the surface temperature of the evaporator increased significantly within 600 seconds after irradiation, and finally stabilized at 37.6±2.4℃ with the extension of irradiation time, which shows that the evaporator has excellent light-heat conversion ability. Figure 3 b shows the mass change curves of the evaporator with different TOCNF concentrations and the corresponding evaporation rates (PTF 0% S 20% 、PTF 2% S 20% 、PTF 4% S 20% and PTF 6% S 20% They represent the evaporators with 0%, 2%, 4%, and 6% TOCNFs addition respectively when the SLS addition is fixed at 20%. As the TOCNFs concentration increases, the evaporator PTF 0% S 20% 、PTF 2% S 20% 、PTF 4% S 20% and PTF 6% S 20% The evaporation rates were 2.88, 3.09, 3.26 and 3.70 kg m -2 h -1 Although the mass fraction of TOCNFs in the solution system is only 6%, the improvement of evaporation rate is significant. Especially when the mass fraction of TOCNF reaches 6%, PTF 6% S 20% The evaporation rate is higher than that of pure water (0.34 kg m -2 h -1 ) is 11 times higher. The effect of TOCNFs on the latent heat of water in the evaporator was further analyzed by dark evaporation experiments ( Figure 3 c) for PTF x S 20% (x represents the mass fraction of TOCNF) evaporator, the latent heat of TOCNFs content increasing from 0wt% to 4wt% is 1146, 1104 and 1037 kJ kg -1 , much lower than pure water (2444kJ kg -1 ). Increasing the mass fraction to 6% results in a PTF 6% S 20% The latent heat is as low as 924 kJ kg -1 Considering the mechanical properties of the evaporator, 6 wt% of TOCNFs was selected as the optimal content.

[0051] 3. Effect of SLS content on evaporation performance of evaporator

[0052] In order to obtain an evaporator with the lowest possible latent heat, the optimal amount of SLS in the system was explored. Figure 4 Figure a shows the temperature change curve of the evaporator under 1 sunlight irradiation. Under 1 sunlight irradiation, the surface temperature of the evaporator increased significantly within 600s after irradiation, and finally stabilized at 37.6±2.4℃ with the extension of irradiation time, which shows that the evaporator has excellent light-heat conversion ability. 6% S y (y represents the mass fraction of SLS) The evaporation rate and latent heat of the evaporator did not increase with the increase of the added amount ( Figure 4 b and c). When the mass fraction of SLS in the evaporator reaches 30%, the evaporation rate decreases significantly to 3.15 kg m -2 h -1 Accordingly, PTF 6% S 30% The latent heat is relatively high, 986 kJ kg -1 . This may be due to the excessive electronegativity of the polymer network repelling the attachment of some SLS particles. In addition, the capillary-induced surface tension in the evaporator channel facilitates the separation of SLS. The exfoliated SLS aggregates in the narrow channels, preventing water vapor from escaping, resulting in a sharp decrease in the evaporation rate. SLS is more effective than TOCNFs in reducing the latent heat of water in the evaporator. PTF 6% S 0% and PTF 6% S 10% The evaporation rates were 2.94 and 3.52 kg m -2 h -1 , the corresponding latent heats are 1153 and 971 kJ kg -1 Based on these results, we choose PTF 6% S 20% As the best evaporator, its power generation performance was further explored.

[0053] 4. Comparison of power generation performance between PTFS evaporator and PVA evaporator

[0054] The distance that ions in solution are negatively charged in the channel (Debye length, λ D ) can be expressed by the Debye-Haack equation. Therefore, the zeta potential plays a crucial role in determining the ability of the solar evaporator to generate streaming potential throughout the evaporation process. Figure 5 As shown in a, PTF 6% S 20% The zeta potential of the evaporator was recorded as -15.2 mV, which exceeded that of the PVA evaporator by about -0.44 mV. The observed effect can be attributed to the PTF6% S 20% There are sufficiently ionized polar groups in the evaporator, including carboxylate groups (-COO - ) functional groups and the sulfonate group (-SO3 - ) group. Experimental data show that PTF 6% S 20% The streaming potential generated by the evaporator can reach a value of about 270 mV, while the streaming potential of the PVA evaporator (without the addition of TOCNFs and SLS) is significantly lower, about 10 mV ( Figure 5 b). The water below the evaporator is brought to the upper surface due to evaporation, the anions (OH-) are rejected, and the H3O + As the water flows upward, a large amount of positive charge accumulates on the upper surface of the evaporator, forming a continuous potential difference between the upper and lower surfaces. 6% S 20% Like an evaporator, it has many microporous channels smaller than the Debye radius, but the channel walls do not contain charged groups, which makes it impossible to capture charged particles in the water flow, thereby forming a potential difference. Figure 5 As shown in c, PTF 6% S 20% The voltage and current of the evaporator under 1 sun illumination were ∼30 mV and 0.06 μA higher than those under dark conditions, respectively. This is because the dense double network structure constructed by TOCNFs and PVA, in which the confined nanochannels retained in the PTF 6% S 20% The water in the evaporator is not sensitive to environmental changes and does not show rapid changes in voltage-environment dependence as membrane-based materials usually do.

[0055] Based on the above research, a better preparation method of a low latent heat solar evaporator is obtained, see the examples for details.

[0056] Example

[0057] A method for preparing a hydrogel evaporator that generates electricity by solar evaporation is as follows:

[0058] (1) Preparation of PTFS suspension:

[0059] 1 g (mass fraction) of PVA was dissolved in 10 g (mass fraction) of deionized water at 90°C and cooled to room temperature. 6 wt% of TOCNFs (1% solid content) and 20 wt% of SLS were added to the PVA solution and mixed thoroughly to prepare a uniform PTF. 6% S 20% Suspension.

[0060] (2) Preparation of PTFS precursor solution:

[0061] 0.125 μl of GA solution with a concentration of 50% was added to the PTFS suspension and stirred for 5 minutes. Subsequently, 1 wt% (i.e. 0.29 g) of PA solution (concentration of 70%) and 2 wt% (i.e. 0.71 g) of CNT solution (concentration of 14%) were added to the PTFS suspension and stirred evenly to prepare a PTFS hydrogel precursor solution.

[0062] (3) Directed freezing of PTFS hydrogel precursor

[0063] The PTFS precursor solution prepared in step (3) is placed in a liquid nitrogen environment, and the precursor solution is directional-frozen from bottom to top through a heat sink, and is taken out after being completely frozen. Finally, freeze-drying is performed at a temperature of -54°C for 48 hours to obtain a PTFS solar evaporator, i.e., a low latent heat solar evaporator for evaporation power generation of the present patent.

[0064] The hydrogel evaporator prepared above was tested as follows:

[0065] The morphology of the samples was observed by scanning electron microscopy (SEM, Hitachi Regulus 8220). The rheological data of the samples were recorded at 25°C using a rheometer (ARES-G2, TA Instruments, USA). The mechanical properties of the samples were studied using a texture meter (TA.XT PlusC, Stable Micro Systems, Surrey, UK).

[0066] The SEM image of the cross section of the prepared evaporator is shown in Figure 6 shown.

[0067] 1. Testing of evaporation performance of hydrogel evaporator indoors and outdoors

[0068] The evaporation rate of the sample was measured using a xenon lamp system (CEL-PE300L-3A) equipped with a CEL-AM1.5 filter. The light intensity on the evaporation surface was quantified using an optical power density meter (CEL-NP2000) and regulated by adjusting the current of the xenon lamp system. The temperature of the evaporation surface was monitored using a thermocouple and recorded every 1 second using a data logger (TC-08). The change in water volume was recorded every 5 seconds using an analytical balance.

[0069] Test results such as Figure 7 As shown, from Figure 7 As can be seen from Figures a and b, the evaporation rate of the evaporator increases with the increase of solar radiation intensity. For 0.5-3 solar radiation, PTF 6% S 20%The evaporation rates of the evaporators were 2.57, 3.70, 6.16, and 8.44 kg m -2 h -1 Even after exposure to 3 suns, PTF 6% S 20% The surface of the PTF remained wet without any salt crystals settling. In addition, in the 10 evaporation cycle test, 6% S 20% The average time for the evaporator to be exposed to sunlight in the salt solution was more than 1 hour. The evaporation rate was stable and there was no obvious difference in appearance, indicating that PTF 6% S 20% The evaporator has the ability to be reused.

[0070] To prove that PTF 6% S 20% The evaporator has excellent evaporation performance in seawater. The evaporation rate ( Figure 7 c). The evaporation rate of the evaporator filled with TOCNFs or SLS is still significantly higher than that of the PVA evaporator and is similar to the evaporation rate in pure water. The evaporation rate of the PVA evaporator under 1 sun irradiation in salt water is 1.42 kg m - 2 h -1 .PTF 6% S 0% The evaporator maintains 2.40 kg m in brine -2 h -1 The evaporation rate of PTF 0% S 20% Evaporation maintains 2.54 kg m -2 h -1 Due to the synergistic effect of TOCNFs and SLS, PTF 6% S 20% The evaporator maintains the highest evaporation rate in salt water, reaching 3.52 kg m under 1 sunlight exposure. -2 h -1 It is noteworthy that the evaporation rate in NaCl solution is slightly reduced compared to pure water, a result that can be attributed to the decrease in vapor pressure caused by the presence of solute.

[0071] To study PTF 6% S 20% The evaporation performance of the evaporator under natural sunlight was investigated, and an outdoor experiment was designed to demonstrate its practical applicability. The outdoor experiment was conducted in Jinan, China, from 10:00 a.m. to 5:00 p.m. on September 25, 2024, when the weather was cloudy. The maximum and minimum solar radiation intensities recorded were 31.8 mW cm -2 and 7.76 mW cm-2 , while the ambient temperature was between a maximum of 30°C and a minimum of 25°C. The solar radiation intensity, evaporator surface temperature, and evaporation rate were examined to evaluate the PTF 6% S 20% Practical application of the evaporator. From 10:00 to 12:00, the solar radiation intensity is 7.76mW cm -2 Increased to 31.8mWcm -1 , resulting in the surface temperature and evaporation rate of the PTFS evaporator increasing from 23.35 °C and 0.21 kg m -2 h -1 Increased to 40.29℃ and 1.86kg m -2 h -1 From 13:00 to 17:00, the solar radiation intensity gradually decreased to 0.56 mW cm -2 , resulting in the surface temperature and evaporation rate of the PTFS evaporator decreasing to 29.19 °C and 0.45 kg m -2 h -1 ( Figure 8 ).

[0072] 2. Testing of the salt removal and seawater desalination capacity of the hydrogel evaporator

[0073] In a sealed container, the PTFS evaporator and pure water are placed together. The bottom of the container contains a supersaturated potassium carbonate solution to maintain a relative humidity of approximately 45%. The experiment was carried out at atmospheric pressure and room temperature (25°C). The latent heat of water in the PTFS evaporator (ΔH eqU ) can be calculated according to the following formula.

[0074] U in =ΔH vap m0=ΔH eqU m g

[0075] Where U in ΔH is the equivalent energy input required for water evaporation. vap and m0 are the latent heat and mass change of bulk water, respectively. ΔH eqU and m g is the latent heat of water and the change in water mass in the cotton stalk evaporator.

[0076] The solar evaporator should be able to discharge salt and desalinate seawater at the same time. 6% S 20% On the surface of the evaporator, it completely disappeared after 1.5 h, which was attributed to PTF 6% S 20% Evaporator's excellent water delivery capacity ( Fig. 9a). Rhodamine B (RhB) and methylene blue (MB) were used to simulate industrial dye wastewater and PTF 6% S 20% After evaporation, colorless and transparent water is obtained. As shown in the UV absorption spectrum ( Fig. 9 b), the dye removal rate is close to 100%, indicating that PTF 6% S 20% Evaporators have the potential for wastewater purification. To verify the PTF 6% S 20% The ability of the evaporator to desalinate seawater will simulate the main ions (Na + , K + , Ca 2+ Mg 2+ and Li + ) concentration was compared with the condensate collected by evaporation ( Fig. 9 c). The concentrations of all major ions have dropped significantly, and the desalted water fully meets the fresh water standards provided by the World Health Organization (WHO).

[0077] 3. Power generation performance test of hydrogel evaporator

[0078] The electrical properties of the evaporator were measured using an electrochemical workstation (CHI660E). Briefly, the evaporator was first cut into a cylinder with a diameter of 1.8 cm and a height of 1 cm, and then inert electrodes were fixed on the upper and lower surfaces of the evaporator, respectively.

[0079] like Fig.10 As shown in a, b, and c, as the load resistance gradually increases, the PTF on the load circuit 6% S 20% The current of the evaporator decreases from 2μA to 0, and the voltage increases from 0mV to 260mV. The output power can be calculated according to the formula P = I 2 ×R L (where I is the current) is calculated. The PTF is observed 6% S 20% The evaporator can achieve a peak output power of 19.06nW at 510KΩ. Under unsealed conditions, PTF 6% S 20% The open circuit voltage of the evaporator remains stable at about 270mV ( Fig.11 ). When PTF 6% S 20% When the evaporator is sealed, the voltage will not drop immediately because the water stored in the evaporator continues to evaporate. Once the sealed device reaches water vapor saturation, PTF 6% S 20% The evaporation of water from the evaporator stops, so the voltage disappears. This observation confirms that capillary water flow is the PTF. 6% S20% The main reason for the voltage generation in the evaporator. 6% S 20% The stability of this streaming potential was further tested by monitoring the voltage of the evaporator. In addition, nine PTFs connected in series 6% S 20% The unit can drive a timer ( Fig.12 ). A hydrophilic polymer with nanoscale charged microchannels was constructed as the substrate of the solar evaporator, and carbon materials were added to achieve fast electron transport and improve the absorbance of the material. Evaporation and power generation were integrated into one device, achieving multi-level energy utilization.

[0080] The embodiments described above are only preferred embodiments of the present invention and are only used to explain the present invention, not to limit the scope of implementation of the present invention. For those skilled in the art, other implementation methods can certainly be easily made by replacement or modification based on the technical contents disclosed in this specification. Therefore, all changes and improvements made on the principles of the present invention should be included in the scope of the patent application of the present invention.

Claims

1. A method for preparing a hydrogel evaporator using solar evaporation to generate electricity, characterized in that: The method comprises the following steps: (1) Preparation of PTFS suspension: PVA was dissolved in deionized water and cooled to room temperature, TOCNFs and SLS were added to the PVA solution and mixed thoroughly to prepare a uniform PTFS suspension; (2) Preparation of PTFS precursor solution: GA solution was added to the PTFS suspension and stirred for 5 minutes, and then 2 wt% of PA solution and 1 wt% of CNT solution were added and stirred evenly to prepare a PTFS hydrogel precursor solution; (3) Directed freezing of PTFS hydrogel precursor The PTFS hydrogel precursor solution prepared in step (3) is placed in a liquid nitrogen environment, and the precursor solution is directionally frozen from bottom to top through a heat sink, and taken out after being completely frozen, and finally, freeze-dried at a temperature of -54°C for 48 hours to obtain a hydrogel evaporator; The PTFS represents polyvinyl alcohol / Tempo oxidized cellulose nanofibers / sodium lignin sulfonate, the TOCNFs are Tempo oxidized cellulose nanofibers, the SLS is sodium lignin sulfonate, the GA is glutaraldehyde, the PA is phytic acid, and the CNT is a multi-walled carbon nanotube dispersion.

2. The preparation method according to claim 1, characterized in that: The specific method for preparing the PTFS suspension is: dissolving 1 part of PVA by mass in 10 parts of deionized water by volume at 90° C., cooling to room temperature, adding 2-6wt% of TOCNFs and 10-30wt% of SLS relative to the mass of the PVA solution to the PVA solution and mixing them thoroughly to prepare a uniform PTFS suspension.

3. The preparation method according to claim 2, characterized in that: The solid content of the TOCNFs is 1%, and the amount of TOCNFs added is 6wt% of the mass of the PVA solution. The amount of SLS added is 20wt% of the mass of the PVA solution.

4. The preparation method according to claim 1, characterized in that: The concentration of the GA solution is 50%, and the volume portion of the added GA solution is 0.125 parts.

5. The preparation method according to claim 1, characterized in that: The concentration of the PA solution is 70%, and the concentration of the CNT solution is 14%.

6. A hydrogel evaporator prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the hydrogel evaporator according to claim 6 in seawater desalination and electricity generation.

Citation Information

Patent Citations

  • PVA hydrogel-based photo-thermal evaporation material and preparation and application thereof

    CN111171340A

  • Cellulose nanofiber aerogel photo-thermal interface water evaporation material and preparation method thereof

    CN114405421A

  • Efficient salt-repellent solar evaporator for heavy salt water treatment and preparation method of efficient salt-repellent solar evaporator

    CN116553667A

  • Preparation method for carbon NANO tube / polyacrylic acid hydrogel, and product and application of carbon NANO tube / polyacrylic acid hydrogel

    WO2023108868A1

Cited By

  • Salt-tolerant hydrogel evaporator for generating power by solar evaporation and preparation method and application thereof

    CN121929771A

  • Honeycomb structure and method for producing same

    WO2026186730A1